Control Strategy of Photovoltaic System to Regulate Active and Reactive Power during Unbalanced Grid Voltages by Using Fuzzy Logic Control - Trilokya, Gujjala; Reddy, M.Rama sekhara (International Journal of Engineering and Technology, 2018)
The advanced reactive power regulation is planned to direct the highest and the voltages at least point of regular pairing inside the cutoff points set up in grid codes for consistent operation. These work displays a regulating technique to which the grid associated PV system meaning to direct the  power of both active and reactive infused to the electrical system amid the voltage faults that are uneven in nature. Fuzzy controller is propel controller which is for the most part appropriate for the personal fundamental guidance tool. which additionally gave the electronic system operation by the master choice. The reference of active power  is acquired from a Maximum Power Point Tracking (MPPT) calculation. The advanced force methodology creates the necessary reference currents that forced by the grid-tied inverter from the coveted P and Q powers and the deliberate voltage supply. In unequal voltage sags, positive and negative sequence KVAr are consolidated to adaptable boost and even out the phase voltages; maximum phase voltage is controlled below as far as possible and the base phase voltage simply over as far as possible. The plan is approved to a solitary step PV system where the currents that are  regulated by means of prescient control. By using the fuzzy controller for a nonlinear system which permit the decrease for the questionable impact in the system which control and impeccably enhance the effectiveness. Results demonstrating the execution of the procedure are introduced amid uneven  sags and swells.